ANALISIS PELAKSANAAN PRAKTIK KERJA LAPANGAN SISWA KELAS XII KOMPETENSI KEAHLIAN AKUNTANSI DI SMK NURUL FALAH PEKANBARU - Emy Dahlia Siregar; Sumarno Sumarno; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine how the practice management at SMKNurul Falah Pekanbaru. This research is a descriptive study, the research is theprincipal, teachers and students. The data collection methods used by researchers wereinterviews and questionnaires. The research istrument use a checklist. The data that hasbeen obtained are analyzed then the percentage is sought. To find out the organization,implementation planning of the percentage of the analysis results the presented with anassessment of the acale rating, while to find out the implementation can also use thesame metthod. With respondents from the results of the research obtained shows thatthe management of on the job training at SMK Nurul Falah Pekanbaru when viewedfrom the organization can run well, indicated by the existence of a street vendororganization structure and task division board, implementation is in progress with moststudents (47,1 %) stated included in the tub and planning category (good), so ifaveraged is good.Key Words: Management, Planning, Implementation, And Evaluation.